The case for economic democracy - Cumbers, Andrew (Cambridge, UK Polity, 2020)
The idea that the people have a right to shape political decisions through democratic means is widely accepted. The same cannot be said of the decisions that impact on our everyday economic life in the workplace and beyond.

Andrew Cumbers shows why this is wrong, and why, in the context of the rising tide of populism and the perceived crisis of liberal democracy, economic democracy's time has come. Four decades of market deregulation, financialisation, economic crisis and austerity has meant a loss of economic control and security for the majority of the world's population. The solution must involve allowing people to 'take back control' of their economic lives. Cumbers goes beyond older traditions of economic democracy to develop an ambitious new framework that includes a traditional concern with workplace rights and collective bargaining, but shifts the focus to include consideration of individual economic rights and processes of public engagement and deliberation beyond the workplace.

This book will be essential reading for anyone interested in radical solutions for our economic and political crises.
Introduction -- A brief history of economic democracy as industrial democracy -- The three pillars of economic democracy -- Putting economic democracy into practice -- Conclusion.
Includes bibliographical references (pages 129-140).
Keywords: Distributive justice; Social justice; Democratization